Activation of EGFR‐Aurora A induces loss of primary cilia in oral squamous cell carcinoma. (16th February 2021) - Yin, Fengying; Chen, Qian; Shi, Yujie; Xu, Hao; Huang, Jie; Qing, Maofeng; Zhong, Liang; Li, Jing; Xie, Liang; Zeng, Xin
Abstract: Objective: Primary cilia, evolutionally conserved organelles involving multiple cell functions, are frequently lost in various cancers. However, little is known about the role of primary cilia in oral squamous cell carcinoma (OSCC). Methods: Immunofluorescence staining was applied to detect primary cilia in normal, oral leukoplakia (OLK) and OSCC tissues. Differentially expressed ciliary genes of OSCC were screened from the TCGA database. Immunohistochemical analysis was used for validating the correlation between the expression of interested proteins and primary cilia, and their regulatory effect on primary cilia was further proved in vitro and in vivo. Results: A significant decrease in cilia ratio was found in OLK, especially in OSCC. Multiple ciliary genes were abnormally expressed in OSCC and epidermal growth factor receptor (EGFR)‐Aurora A signaling was chosen for further study. A parallel increase of EGFR‐Aurora A was observed in OLK and OSCC tissues. Moreover, EGFR activation induced obvious cilia absorption by phosphorylating Aurora A. Besides, Aurora A silencing significantly restored ciliary expression and decreased tumor growth in vivo. Conclusions: The abnormal activation of EGFR‐Aurora A leads to the gradual loss of primary cilia in oral mucosa carcinogenesis. Primary cilia have the potential to be new biomarkers and therapeutic targets of oral cancer.